A 4.8-μVrms-Noise CMOS-Microelectrode Array With Density-Scalable Active Readout Pixels via Disaggregated Differential Amplifier Implementation - Jun Ogi; Yuri Kato; Yusaku Nakashima; Kenji Ikeda; Motoko Jingu; Yoshihisa Matoba; Naohiko Kimizuka; Chigusa Yamane; Masataka Maehara; Takuya Kishimoto; Shigeki Hashimoto; Eriko Matsui; et al. (Frontiers in Neuroscience, 2019)
We demonstrate a 4.8-μVrms noise microelectrode array (MEA) based on the complementary-metal-oxide-semiconductor active-pixel-sensors readout technique with disaggregated differential amplifier implementation. The circuit elements of the differential amplifier are divided into a readout pixel, a reference pixel, and a column circuit. This disaggregation contributes to the small area of the readout pixel, which is less than 81 μm2. We observed neuron signals around 100 μV with 432 electrodes in a fabricated prototype chip. The implementation has technological feasibility of up to 12-μm-pitch electrode density and 6,912 readout channels for high-spatial resolution mapping of neuron network activity.